Flying Under Surveillance: Social Acceptance and Implementation Dynamics of Standard Screening Requirements in Indonesian Aviation Security - Dian Wahyudi; Muhammad Zilal Hamzah; Eleonoro Sofilda (Journal of General Education and Humanities, 2026)
Air transportation relies on Standard Screening Requirements (SSR) to ensure safety, inherently placing passengers under intensive surveillance. This research analyzes the implementation dynamics of SSR in Indonesia through an integrative qualitative approach. Primary data was gathered via Focus Group Discussions (FGDs) with key aviation stakeholders comprising regulators, airport operators, airlines, technology providers, and users, and analyzed using NVivo thematic coding. This was triangulated with a Systematic Literature Review (SLR) of 58 eligible articles to synthesize global perspectives on passenger surveillance. The findings demonstrate that SSR effectiveness depends heavily on aligning human resource capacity, standardized infrastructure, and stakeholder synergy. While the public broadly accepts these security measures when conducted seamlessly and professionally, significant challenges persist due to regional infrastructure disparities and capacity constraints across Indonesia's complex geography. Ultimately, this study contributes to the literature by proposing an integrative socio-technical framework, demonstrating that equitable infrastructure modernization and collaborative governance are essential to sustaining operational efficiency and promoting security-led economic growth.